Electrode composition for lithium ion battery, electrode for lithium ion battery, and lithium ion battery
By using an ethylene oxide adduct of an alkyl alcohol with a specific carbon-to-ethylene oxide ratio in the electrode composition, the challenges of enhancing electrolyte permeability in lithium ion batteries are addressed, resulting in improved electrolyte permeation rates and battery performance.
Patent Information
- Application Number
- JP2024110863
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-12
- Filing Date
- 2024-07-10
- Publication Date
- 2025-01-24
AI Technical Summary
Existing methods for improving electrolyte permeability in lithium ion batteries, such as those described in Patent Documents 1, 2, and 3, either require new equipment or do not sufficiently enhance electrolyte permeation rates, leading to suboptimal battery performance when electrode density is increased.
Incorporating an ethylene oxide adduct of an alkyl alcohol with 1 to 4 carbon atoms in the electrode composition, where the ratio of carbon atoms in the alkyl group to the average number of added moles of ethylene oxide ranges from 0.008 to 0.200, to enhance electrolyte permeability and permeation rate.
The solution results in a lithium ion battery electrode with high electrolyte permeability and fast electrolyte permeation rates, maintaining or improving battery performance even at higher densities.
Smart Images

Figure 2025013266000001 
Figure 2025013266000002 
Figure 2025013266000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode composition for a lithium ion battery, an electrode for a lithium ion battery, and a lithium ion battery. [Background technology]
[0002] Lithium-ion batteries, which have the characteristics of high voltage and high energy density, are widely used in the field of portable information devices, and have established their position as the standard battery for portable terminals such as mobile phones and notebook computers. As their uses expand, their application to hybrid and electric vehicles, in addition to the conventional applications, is being considered, and some have already been put into practical use. In order to further popularize these, there is a demand for lithium-ion batteries with higher capacity and power output, and various technologies are being attempted to apply them.
[0003] One method to improve the capacity of secondary batteries is to increase the electrode density. By densely packing the active material, more capacity can be obtained. However, increasing the density of the electrodes makes it difficult for the electrolyte to penetrate into the electrodes, resulting in problems such as less capacity than the theoretical value being obtained and deterioration of output characteristics.
[0004] To solve these problems, Patent Document 1 discloses a technique for improving electrolyte permeability by providing grooves on the electrode surface. Patent Document 2 discloses a technique for improving electrolyte permeability by adjusting the particle size and shape of the active material. Patent Document 3 discloses a technique for improving electrolyte permeability by adjusting the electrode density. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2008-27633 A [Patent Document 2] JP 2012-151088 A [Patent Document 3] JP 2020-053282 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the method of Patent Document 1 involves a process of pressing the electrode surface with a roller having projections and recesses in order to form grooves on the surface, which necessitates the introduction of new equipment, which is a problem. In addition, although the techniques of Patent Documents 2 and 3 show some improvement in permeability, the effect is not sufficient.
[0007] The present invention has been made to solve the above problems, and has an object to provide an electrode composition for lithium ion batteries that can produce an electrode having high electrolyte permeability and a high electrolyte permeation rate. [Means for solving the problem]
[0008] As a result of extensive investigations, the present inventors arrived at the present invention. The present invention provides an electrode composition for a lithium ion battery, comprising a compound (A) which is an ethylene oxide adduct of an alkyl alcohol having an alkyl group with 1 to 4 carbon atoms, The present invention relates to an electrode composition for lithium ion batteries, in which the ratio of the number of carbon atoms in the alkyl group in the compound (A) to the average number of moles of ethylene oxide added [number of carbon atoms in the alkyl group / average number of moles of ethylene oxide added] is 0.008 to 0.200; an electrode for lithium ion batteries obtained by compression molding the electrode composition for lithium ion batteries; and a lithium ion battery comprising the electrode for lithium ion batteries. Effect of the Invention
[0009] According to the present invention, it is possible to provide an electrode composition for a lithium ion battery that can produce an electrode having high electrolyte permeability and a high electrolyte permeation rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Electrode composition for lithium ion batteries] The electrode composition for lithium ion batteries of the present invention relates to an electrode composition for lithium ion batteries containing compound (A) which is an ethylene oxide adduct of an alkyl alcohol having an alkyl group with 1 to 4 carbon atoms, wherein the ratio of the number of carbon atoms in the alkyl group in compound (A) to the average number of moles of ethylene oxide added [number of carbon atoms in alkyl group / average number of moles of ethylene oxide added] is 0.008 to 0.200. Hereinafter, the "lithium ion battery electrode composition" will also be referred to as the "electrode composition."
[0011] In the present invention, the electrode composition means a composition that becomes an electrode by compression molding. The electrode composition of the present invention does not contain an electrolyte solution itself, but as described below, an electrode prepared using the electrode composition can be made into an electrode layer for a lithium ion battery by adding an electrolyte solution to the electrode. The electrode composition of the present invention may be an electrode composition for a positive electrode (also referred to as a positive electrode composition) or an electrode composition for a negative electrode (also referred to as a negative electrode composition).
[0012] Compound (A) is an ethylene oxide adduct of an alkyl alcohol having an alkyl group with 1 to 4 carbon atoms. When the alkyl group has 5 or more carbon atoms, the adsorption to the active material is low, and the effect of improving the electrolyte permeability is not obtained. In addition, the dispersibility in the electrode composition for lithium ion batteries is poor, which may adversely affect the battery performance, or may deteriorate the coating property on the current collector surface and the surface condition of the electrode in the slurry electrode described below. In addition, when the alkyl group is not present, the adsorption to the active material is difficult, and the effect of improving the electrolyte permeability is not obtained. If an alkylene oxide other than ethylene oxide (such as propylene oxide and butylene oxide) is contained, the electrolyte permeability becomes insufficient when the porosity of the electrode described below is relatively low (approximately 25% or less). In the present specification, alkylene oxide may be abbreviated as AO, ethylene oxide as EO, and propylene oxide as PO.
[0013] Specific examples of alkyl alcohols in which the alkyl group has 1 to 4 carbon atoms include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 2-methyl-1-propanol (isobutyl alcohol), and 2-methyl-2-propanol (t-butyl alcohol). From the viewpoint of compatibility between the coating property of the slurry electrode on the current collector surface and the surface condition and electrolyte permeability of the electrode, the alkyl group of the alkyl alcohol preferably has 1 to 3 carbon atoms, and more preferably 1 to 2 carbon atoms.
[0014] The alkyl group of the alkyl alcohol may be either straight chain or branched chain. In addition, from the viewpoint of electrolyte permeability when the porosity of the electrode described later is relatively low (about 25% or less), the number of methyl groups possessed by the alkyl alcohol constituting all the compounds (A) contained in the lithium ion battery electrode composition is preferably 1 to 2. Specifically, among the above examples, methanol (number of methyl groups: 1), ethanol (number of methyl groups: 1), 1-propanol (number of methyl groups: 1), 2-propanol (number of methyl groups: 2), 1-butanol (number of methyl groups: 1), 2-butanol (number of methyl groups: 2), and 2-methyl-1-propanol (isobutyl alcohol) (number of methyl groups: 2) are preferred. The number of carbon atoms in the alkyl group of the alkyl alcohol and the number of methyl groups in the alkyl alcohol are, for example, 1 It can be calculated by measuring H-NMR and gas chromatography.
[0015] The ratio of the number of carbon atoms in the alkyl group to the average number of moles of ethylene oxide added in the compound (A) [number of carbon atoms in the alkyl group / average number of moles of ethylene oxide added] is 0.008 to 0.200. If the ratio of the number of carbon atoms in the alkyl group to the average number of moles of ethylene oxide added is less than 0.008, the frequency of adsorption to the active material decreases, and the permeability into the active material decreases, so the electrolyte permeation rate tends to decrease. On the other hand, if the ratio exceeds 0.200, the affinity with the electrolyte decreases, so the electrolyte permeation rate tends to decrease. In addition, the ratio of the number of carbon atoms in the alkyl group to the average number of moles of ethylene oxide added is preferably 0.008 to 0.180, more preferably 0.010 to 0.180, more preferably 0.020 to 0.180, even more preferably 0.020 to 0.150, and most preferably 0.040 to 0.150, from the viewpoints of electrolyte permeability and coatability onto the current collector surface in a slurry electrode.
[0016] From the viewpoint of electrolyte permeability and the like, the HLB value of the compound (A) is preferably 18.0 or more, more preferably 18.0 to 22.0, particularly preferably 18.6 to 21.0, and most preferably 19.0 to 20.5. When two or more compounds (A) are used in combination, the HLB value of the mixture of two or more compounds (A) is preferably within the above range. The HLB value of the mixture of two or more compounds (A) is the weighted average of the HLB values of the individual compounds (A) based on their weight ratios.
[0017] HLB is a scale showing the balance between hydrophilicity and lipophilicity, and the higher the HLB, the higher the hydrophilicity. For example, it is known as a value calculated by the Oda method described in "Introduction to Surfactants, 2007, Sanyo Chemical Industries Co., Ltd., Takehiko Fujimoto, p. 212," and is not a value calculated by the Griffin method. The HLB value can be calculated from the ratio of the organic value to the inorganic value of an organic compound. HLB value = 10 x inorganic / organic Here, the inorganic and organic values in the above formula represent index values expressing organic and inorganic properties proposed by Fujita et al., and can be calculated using the values in the table on page 213 of the aforementioned "Introduction to Surfactants."
[0018] A specific example of the compound (A) in the present invention is an ethylene oxide adduct of methanol (alkyl group carbon number: 1). In this case, the average number of moles of ethylene oxide added is 5 to 125, preferably 5 to 45, and more preferably 8 to 20.
[0019] Another specific example of the compound (A) is an ethylene oxide adduct of ethanol (alkyl group carbon number: 2). In this case, the average number of moles of ethylene oxide added is 10 to 250, preferably 10 to 120, more preferably 13 to 100, and particularly preferably 20 to 60.
[0020] Another specific example of the compound (A) is an ethylene oxide adduct of 1-propanol (alkyl group carbon number: 3). In this case, the average number of moles of ethylene oxide added is 15 to 375, and preferably 20 to 200.
[0021] Another specific example of the compound (A) is an ethylene oxide adduct of 2-propanol (alkyl group carbon number: 3). In this case, the average number of moles of ethylene oxide added is 15 to 375, and preferably 20 to 200.
[0022] Another specific example of the compound (A) is an ethylene oxide adduct of 1-butanol (alkyl group carbon number: 4). In this case, the average number of moles of ethylene oxide added is 20 to 500, and preferably 20 to 200.
[0023] Another specific example of the compound (A) is an ethylene oxide adduct of 2-butanol (alkyl group carbon number: 4). In this case, the average number of moles of ethylene oxide added is 20 to 500, and preferably 20 to 200.
[0024] Another specific example of the compound (A) is an ethylene oxide adduct of 2-methyl-1-propanol (isobutyl alcohol) (alkyl group carbon number: 4). In this case, the average number of moles of ethylene oxide added is 20 to 500, and preferably 20 to 200.
[0025] Another specific example of the compound (A) is an ethylene oxide adduct of 2-methyl-2-propanol (t-butyl alcohol) (alkyl group carbon number: 4). In this case, the average number of moles of ethylene oxide added is 20 to 500, and preferably 20 to 200.
[0026] In the present invention, compound (A) means an ethylene oxide adduct having the same carbon number and structure as the starting alkyl alcohol, and is an ethylene oxide adduct of methanol, an ethylene oxide adduct of ethanol, an ethylene oxide adduct of 1-propanol, an ethylene oxide adduct of 2-propanol, an ethylene oxide adduct of 1-butanol, an ethylene oxide adduct of 2-butanol, an ethylene oxide adduct of 2-methyl-1-propanol, or an ethylene oxide adduct of 2-methyl-2-propanol. The electrode composition for lithium ion batteries of the present invention may contain only one type of compound (A), or may contain multiple compounds (A) with different carbon numbers or structures of alkyl alcohols, which are raw materials for the ethylene oxide adduct. For example, an ethylene oxide adduct of methanol and an ethylene oxide adduct of ethanol may be used in combination. However, when multiple types of compounds (A) are used in combination, the ratio of the number of carbon atoms in the alkyl group to the average number of moles of ethylene oxide added in each compound (A) [number of carbon atoms in the alkyl group / average number of moles of ethylene oxide added] is 0.008 to 0.200.
[0027] In the electrode composition for lithium ion batteries, as ingredients contained in addition to the compound (A), known materials constituting electrode compositions for lithium ion batteries can be used. The electrode composition for lithium ion batteries contains at least an electrode active material. The electrode active material may be a positive electrode active material or a negative electrode active material. When the electrode active material is a positive electrode active material, the electrode composition for a lithium ion battery of the present invention can be used as a positive electrode composition for a lithium ion battery, and when the electrode active material is a negative electrode active material, the electrode composition for a lithium ion battery of the present invention can be used as a negative electrode composition for a lithium ion battery.
[0028] There are no particular limitations on the positive electrode active material as long as it can be used as a positive electrode active material for a lithium ion battery. For example, composite oxides of lithium and transition metals {composite oxides containing one type of transition metal (e.g., LiCoO2, LiNiO2, LiAlMnO4, LiMnO2, and LiMn2O4), composite oxides containing two types of transition metal elements (e.g., LiFeMnO4, LiNi 1-x Co x O2, LiMn 1-y Co y O2, LiNi 1 / 3 Co 1 / 3 Al 1 / 3 O2 and LiNi 0.8 Co 0.15 Al 0.05 O2) and composite oxides containing three or more transition metal elements [e.g. LiM a M' b M'' c O2(M, M' and M'' are different transition metal elements and satisfy a+b+c=1. For example, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3Examples of the conductive polymer include lithium-containing transition metal phosphates (e.g., LiFePO4, LiCoPO4, LiMnPO4, and LiNiPO4), transition metal oxides (e.g., MnO2 and V2O5), transition metal sulfides (e.g., MoS2 and TiS2), and conductive polymers (e.g., polyaniline, polypyrrole, polythiophene, polyacetylene, poly-p-phenylene, and polyvinylcarbazole), and two or more of these may be used in combination. The lithium-containing transition metal phosphate may have some of the transition metal sites substituted with other transition metals. When the electrode active material is a positive electrode active material, a composite oxide of lithium and a transition metal or a lithium-containing transition metal phosphate is particularly preferred.
[0029] There are no particular limitations on the negative electrode active material as long as it can be used as a negative electrode active material for a lithium ion battery. For example, carbon-based materials [graphite, non-graphitizable carbon (hard carbon), amorphous carbon, resin baked bodies (e.g., phenolic resin, furan resin, etc. baked and carbonized), cokes (e.g., pitch coke, needle coke, petroleum coke, etc.), and carbon fibers, etc.] and silicon-based materials [silicon, silicon oxide (SiO x ), silicon-carbon composites (carbon particles whose surfaces are coated with silicon and / or silicon carbide, silicon particles or silicon oxide particles whose surfaces are coated with carbon and / or silicon carbide, silicon carbide, etc.), and silicon alloys (silicon-aluminum alloy, silicon-lithium alloy, silicon-nickel alloy, silicon-iron alloy, silicon-titanium alloy, silicon-manganese alloy, silicon-copper alloy, silicon-tin alloy, etc.). The conductive material may be a mixture of a carbon-based material with a conductive polymer (e.g., polyacetylene, polypyrrole, etc.), a metal (tin, aluminum, zirconium, titanium, etc.), a metal oxide (titanium oxide, lithium-titanium oxide, etc.), and a metal alloy (e.g., lithium-tin alloy, lithium-aluminum alloy, lithium-aluminum-manganese alloy, etc.). When the electrode active material is a negative electrode active material, the negative electrode active material is preferably a carbon-based material, and particularly preferably graphite or hard carbon.
[0030] The electrode composition for lithium ion batteries of the present invention can provide a particularly excellent effect of improving electrolyte permeability when used in combination with an electrode active material having a layered structure (e.g., a metal oxide, graphite, or hard carbon having a layered rock salt structure).
[0031] The lithium ion battery electrode composition of the present invention is particularly effective in improving electrolyte permeability when the electrode active material has a volume average particle diameter (Dv50) of 6.0 to 20.0 μm.
[0032] In addition, the lithium ion battery electrode composition may contain a conductive assistant, a binder resin, and a thickener, or may not contain any of these components. Examples of the conductive assistant include metals [aluminum, stainless steel (SUS), silver, gold, copper, titanium, etc.], carbon [graphite (flaky graphite (UP)), carbon black (acetylene black, ketjen black, furnace black, channel black, thermal lamp black, etc.) and carbon nanofibers (CNF), etc.], and mixtures thereof. As the conductive assistant, carbon black and carbon nanotubes are preferred from the viewpoint of electrical stability.
[0033] The binder resin is not particularly limited as long as it is a resin having a binder function (adhesive strength). Examples of the binder resin include starch, polyvinylidene fluoride (PVdF), polyvinyl alcohol, polyvinylpyrrolidone, polytetrafluoroethylene, tetrafluoroethylene, polyacrylic acid, sodium polyacrylate, polyacrylic acid ester, polymethacrylic acid ester, styrene-butadiene rubber (SBR), polyethylene, and polypropylene. The binder resin broadly includes a thickener, and an example of the thickener is carboxymethyl cellulose (CMC).
[0034] In addition, carbon-based materials are used both as negative electrode active materials and conductive assistants, but in this application, those with a volume average particle diameter of 5 μm or more are considered to be negative electrode active materials, and those with a volume average particle diameter of less than 5 μm are considered to be conductive assistants.
[0035] In this specification, the volume average particle size refers to the particle size (Dv50) at an integrated value of 50% in the particle size distribution determined by the Microtrack method (laser diffraction / scattering method). The Microtrack method is a method for determining the particle size distribution by utilizing scattered light obtained by irradiating particles with laser light. The volume average particle size can be measured using a Microtrack manufactured by Nikkiso Co., Ltd.
[0036] The content of compound (A) in the lithium ion battery electrode composition of the present invention is preferably 0.001 to 2% by weight based on the weight of the lithium ion battery electrode composition. When the content of compound (A) is within this range, the effect of including compound (A) can be more suitably exhibited.
[0037] [Electrodes for lithium-ion batteries] The lithium ion battery electrode of the present invention is produced by compression molding the lithium ion battery electrode composition of the present invention. When the electrode composition is a slurry electrode composition containing a solvent, it is preferable to remove the solvent by drying before compression molding (hereinafter, an electrode manufactured via a slurry electrode composition containing a solvent may be referred to as a "slurry electrode"). The lithium ion battery electrode of the present invention may be the above-mentioned slurry electrode, or an electrode produced by a dry process that does not use a solvent (hereinafter, sometimes referred to as a "dry electrode"). When the lithium ion battery electrode of the present invention is a dry electrode, it is not particularly limited, but a dry electrode containing a fibrillated resin such as polytetrafluoroethylene resin (PTFE) as a binder resin is preferred, as in the secondary battery electrode described in JP 2022-103141 A. Also preferred is a dry electrode containing coated negative electrode active material particles for lithium ion batteries and a conductive filler, as in the lithium ion battery negative electrode described in JP 2023-163593 A.
[0038] The method for compression molding the lithium ion battery electrode composition is not particularly limited, and methods such as roll pressing, pressing with a press machine, etc. can be used. The porosity (sometimes referred to as "electrode porosity" in this specification) (%) of the electrode active material layer of the lithium ion battery electrode obtained by compression molding the lithium ion battery electrode composition is preferably 15 to 40%, particularly preferably 17 to 36%, from the viewpoint of the performance (energy density, output characteristics, etc.) of the lithium ion battery. A lithium ion battery electrode obtained using the lithium ion battery electrode composition of the present invention has excellent electrolyte permeability even in the case of a low porosity (approximately 25% or less) where electrolyte permeability generally tends to deteriorate. In the present invention, the porosity of the electrode means the porosity in a state where the lithium ion battery electrode composition is not permeated with an electrolyte, and is measured by the following method.
[0039] (Method for measuring the porosity of the electrode active material layer of the electrode) The porosity of the electrode active material layer is calculated according to the following formula (1). Equation (1): Porosity (%) = 100 - volume ratio of solid matter in electrode active material layer (%) Here, the "solid content volume ratio (%)" of the electrode active material layer is calculated by the following formula (2). Equation (2): Solid volume fraction (%) = (solid material volume (cm 3 ) / electrode active material layer volume (cm 3 ))×100 The volume of the electrode active material layer is calculated from the thickness of the electrode (measured with a contact type film thickness meter) and the coating area. The volume of the solid material is calculated by the following procedure. (a) Weigh out the amount of each material added to the electrode active material layer slurry: (b) Measure the weight of the current collector before coating: (c) After the slurry for the electrode active material layer is applied to the surface of the current collector, the weight of the current collector and the coating film are weighed: (d) The applied slurry is pre-dried overnight in a draft, and then further dried at 100°C under reduced pressure (1.3 kPa) for 2 hours, after which it is pressed, and the weights of the pressed current collector and coating film are weighed. (e) From the values of (a), (b), (c), and (d), calculate the weight of each material in the electrode active material layer after pressing: (f) From the weight and density of each material calculated in (e), the volume of each material in the electrode active material layer is calculated: (g) Calculate the volume of solid ingredients by adding up only the volumes of solid ingredients among the volumes of each ingredient calculated in (f).
[0040] [Lithium-ion battery] The lithium ion battery of the present invention comprises the lithium ion battery electrode of the present invention.
[0041] The lithium ion battery of the present invention is equipped with the lithium ion battery electrode of the present invention, and since the electrolyte solution sufficiently permeates into the electrode, it has excellent charge / discharge efficiency (Coulombic efficiency).
[0042] For the components constituting the lithium ion battery of the present invention, other than the electrodes for the lithium ion battery, known materials can be used. That is, known materials can be used as the materials for the current collector, the electrolyte, the separator, and the like.
[0043] As the electrolytic solution, it is preferable to use a carbonate-based nonaqueous solvent (ethylene carbonate, diethyl carbonate, propylene carbonate, etc.) as the nonaqueous solvent. The nonaqueous solvent may be used alone or in combination of two or more. It is preferable to use LiPF6 (lithium hexafluorophosphate), LiFSI (lithium bis(fluorosulfonyl)imide), etc. as the electrolyte. The electrolytic solution is obtained by dissolving the electrolyte in the nonaqueous solvent at room temperature or by heating as necessary. Commercially available products may be used. The electrode composition for lithium ion batteries of the present invention is widely applicable not only to lithium ion batteries using a specific electrolyte but also to lithium ion batteries using an electrolyte solution containing the above-mentioned representative electrolytes, and can improve the electrolyte permeation rate.
[0044] The lithium ion battery of the present invention is particularly effective in improving the electrolyte permeability when the electrolyte constituting the lithium ion battery has a viscosity of 6.0 to 12.0 mPa s at 25° C. The viscosity of the electrolyte at 25° C. can be measured using a B-type viscometer (for example, a "BLII type viscometer" manufactured by Toki Sangyo Co., Ltd.) or the like.
[0045] In the lithium ion battery of the present invention, only the positive electrode may be composed of the lithium ion battery electrode of the present invention, only the negative electrode may be composed of the lithium ion battery electrode of the present invention, or both the positive electrode and the negative electrode may be composed of the lithium ion battery electrode of the present invention.
[0046] The lithium ion battery of the present invention can be used as a lithium ion battery for use in mobile phones, personal computers, hybrid cars, electric cars, stationary power sources, and the like.
[0047] [Method of manufacturing electrode composition for lithium ion batteries] The electrode composition for lithium ion batteries of the present invention can be obtained by mixing compound (A) with other components (electrode active material and, if necessary, components such as a conductive assistant and a binder resin (including a thickener)). The mixing method and mixing order of each component are not particularly limited, but in the case where both styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are contained, it is preferable not to add and mix SBR and CMC at the same time from the viewpoint of uniformity of the electrode composition. For example, a preferred method is to stir and homogenize the conductive assistant, CMC, and if necessary a solvent, add and mix SBR, and then further add and mix compound (A) and the electrode active material. Moreover, the compound (A) can be obtained by carrying out a reaction in which ethylene oxide is added to an alkyl alcohol having an alkyl group with 1 to 4 carbon atoms by a known method.
[0048] The present specification discloses the following:
[0049] The present disclosure (1) provides an electrode composition for a lithium ion battery, comprising a compound (A) which is an ethylene oxide adduct of an alkyl alcohol having an alkyl group with 1 to 4 carbon atoms, In the electrode composition for lithium ion batteries, the ratio of the number of carbon atoms in the alkyl group in the compound (A) to the average number of moles of ethylene oxide added [number of carbon atoms in the alkyl group / average number of moles of ethylene oxide added] is 0.008 to 0.200.
[0050] The present disclosure (2) is the electrode composition for a lithium ion battery according to the present disclosure (1), in which the HLB value of the compound (A) is 18.0 or more.
[0051] The present disclosure (3) is the electrode composition for lithium ion batteries according to the present disclosure (1) or (2), in which the content of the compound (A) is 0.001 to 2% by weight based on the weight of the electrode composition for lithium ion batteries.
[0052] The present disclosure (4) is a lithium ion battery electrode obtained by compression molding the lithium ion battery electrode composition according to any one of the present disclosures (1) to (3).
[0053] The present disclosure (5) is a lithium ion battery including the lithium ion battery electrode according to the present disclosure (4). EXAMPLES
[0054] The present invention will now be described in detail with reference to examples. However, the present invention is not limited to these examples as long as it does not depart from the gist of the present invention.
[0055] (Production Example 1: Production of Compound (A-1)) Ethylene oxide (EO) was added to methanol to produce compound (A-1), an ethylene oxide adduct of methanol. The average number of moles of ethylene oxide added (hereinafter, the average number of moles of EO added) was 8.6. The ratio of the number of carbon atoms in the alkyl group to the average number of moles of ethylene oxide added [number of carbon atoms in the alkyl group / average number of moles of EO added] was 0.116. The HLB was 20.5.
[0056] (Production Examples 2 to 9: Production of Compounds (A-2) to (A-9)) Compounds (A-2) to (A-9) were produced in the same manner as in Production Example 1, except that the type of alkyl alcohol and the average number of moles of EO added were changed as shown in Table 1.
[0057] (Production Example 10: Preparation of Compound (A-10)) Polyethylene glycol having an average EO addition mole number of 45 (product name "PEG-2000", manufactured by Sanyo Chemical Industries, Ltd.) was prepared as a comparative compound (Comparative A-1).
[0058] (Production Examples 11 to 13 and 15 to 17: Production of Compounds (Comparative A-2) to (Comparative A-4) and (Comparative A-6) to (Comparative A-8)) Comparative compounds (Comparative A-2) to (Comparative A-4) and (Comparative A-6) to (Comparative A-8) were produced in the same manner as in Production Example 1, except that the type of alkyl alcohol and the average number of moles of EO added were changed as shown in Table 1.
[0059] (Production Example 14: Production of Compound (Comparative A-5)) Propylene oxide (PO) was added to methanol to produce a comparative compound (Comparative A-5) which is a propylene oxide adduct of methanol. The average number of moles of EO added was 0.0, and the average number of moles of propylene oxide added was 6.5.
[0060] The [number of carbon atoms in alkyl group / average number of moles of EO added] and HLB value of the compounds obtained in each production example are shown in Table 1.
[0061] [Table 1]
[0062] (Preparation of positive electrode active material) The following positive electrode active materials were prepared. NCA:LiNi 0.8 Co 0.15 Al 0.05 O2 ("HED NCA 7050", manufactured by BASF Toda Battery Materials LLC, volume average particle size (Dv50) 6.6 μm) LFP: Lithium iron phosphate ("LCP420TU4", manufactured by Sumitomo Osaka Cement Co., Ltd., volume average particle size (Dv50) 8.7 μm)
[0063] (Examples 1 to 12 and Comparative Examples 1 to 11: Preparation of Slurry Electrode (Positive Electrode)) The compound {(A) or (comparison A)} in the weight parts shown in Table 2 or Table 3 and 100.0 weight parts of N-methyl-2-pyrrolidone (NMP) were mixed at 2000 rpm for 5 minutes using a planetary mixing type mixing and kneading device {Awatori Rentaro [manufactured by Thinky Corporation]}. Next, 3.0 weight parts of polyvinylidene fluoride (referred to as "PVdF" in Tables 2 and 3, manufactured by Kishida Chemical) as a binder resin were added, and the mixture was mixed at 2000 rpm for 5 minutes using the Awatori Rentaro. Furthermore, NCA and a conductive assistant as a positive electrode active material in the weight parts shown in Table 2 or Table 3 were added, and the mixture was mixed at 2000 rpm for 4 minutes using the Awatori Rentaro to prepare a slurry for a positive electrode active material layer (positive electrode composition). As the conductive assistant, acetylene black "Denka Black Li100" (referred to as "AB" in Tables 2 and 3, manufactured by Denka Co., Ltd.) was used. The obtained slurry for the positive electrode active material layer was applied to one side of a current collector (aluminum foil, manufactured by Hosen Co., Ltd.) using a wire bar in the atmosphere, pre-dried overnight in a draft, and then punched out into six pieces of 15 mm diameter, which were further dried at 100°C under reduced pressure (1.3 kPa) for 2 hours and pressed with a press until the target electrode porosity (electrode thickness) was reached to prepare a positive electrode for evaluation. Six positive electrodes for evaluation were prepared for each Example and Comparative Example (except Comparative Example 9), three of which were used for evaluation of the surface condition and electrolyte permeability, and the remaining three were used for evaluation of the battery performance (initial coulombic efficiency, internal resistance). In addition, Comparative Example 9 is an electrode composition and an electrode (positive electrode) that do not contain either the compound (A) or the compound (comparison A). The required number of electrodes (positive electrodes) of Comparative Example 9 were prepared.
[0064] (Examples 13 to 15 and Comparative Examples 12 to 14: Preparation of Slurry Electrode (Positive Electrode)) The weight parts of the compound {(A) or (Ratio A)} listed in Table 2 or Table 3 and 100.0 weight parts of water were mixed at 2000 rpm for 5 minutes using a planetary mixing type mixing and kneading device {Awatori Rentaro [manufactured by Thinky Corporation]}. Next, 3.0 weight parts of polyacrylic acid (referred to as "PAA" in Tables 2 and 3, manufactured by Sigma-Aldrich, average molecular weight approximately 100,000) as a binder resin were added, and the mixture was stirred at 2000 rpm for 5 minutes using the Awatori Rentaro. Furthermore, the weight parts of LFP and conductive assistant as a positive electrode active material listed in Table 2 or Table 3 were added, and the mixture was stirred at 2000 rpm for 4 minutes using the Awatori Rentaro to prepare a slurry for a positive electrode active material layer (positive electrode composition). As the conductive assistant, acetylene black "Denka Black Li100" (referred to as "AB" in Tables 2 and 3, manufactured by Denka Co., Ltd.) was used. The obtained slurry for the positive electrode active material layer was applied to one side of a current collector (aluminum foil, manufactured by Hosen Co., Ltd.) using a wire bar in the atmosphere, pre-dried overnight in a draft, and then punched out into six pieces of 15 mm diameter, which were further dried at 100°C under reduced pressure (1.3 kPa) for 2 hours and pressed with a press until the target electrode porosity (electrode thickness) was reached to prepare a positive electrode for evaluation. Six positive electrodes for evaluation were prepared for each Example and Comparative Example (except Comparative Example 14), three of which were used for evaluation of the surface condition and electrolyte permeability, and the remaining three were used for evaluation of the battery performance (initial coulombic efficiency, internal resistance). In addition, Comparative Example 14 is an electrode composition and an electrode (positive electrode) that do not contain either compound (A) or (comparison A). The required number of electrodes (positive electrodes) of Comparative Example 14 were prepared.
[0065] [Table 2]
[0066] [Table 3]
[0067] (Preparation of negative electrode active material) The following negative electrode active materials were prepared. Spherical graphite: "CGB-20", manufactured by Nippon Graphite Co., Ltd., volume average particle size (Dv50) 20 μm Artificial graphite: "PAG-1500", manufactured by Nippon Graphite Co., Ltd., volume average particle size (Dv50) 10 μm
[0068] (Examples 16-30, Comparative Examples 15-28: Preparation of Slurry Electrode (Negative Electrode)) 2.0 parts by weight of AB {acetylene black: "Denka Black Li100", manufactured by Denka Co., Ltd.} as a conductive assistant, 3.0 parts by weight of CMC (carboxymethyl cellulose) as a binder resin, and 40.0 parts by weight of ion-exchanged water were stirred at 2000 rpm for 5 minutes using a planetary stirring type mixing kneader {Awatori Rentaro [manufactured by Thinky Corporation]}. Next, 3.0 parts by weight of SBR (styrene butadiene rubber) as a binder resin was added, and stirring was performed with the Awatori Rentaro at 2000 rpm for 5 minutes. 92.0 parts by weight of an electrode active material shown in Table 4 or Table 5, a compound {(A) or (comparison A)} shown in Table 4 or Table 5 in a weight part, and 60.0 parts by weight of ion-exchanged water were added to the obtained dispersion, and stirring was performed with the Awatori Rentaro at 2000 rpm for 5 minutes to prepare a slurry for a negative electrode active material layer (negative electrode composition). The obtained slurry for the negative electrode active material layer was applied to one side of a current collector (copper foil) using a wire bar in the atmosphere, pre-dried overnight in a draft, and then punched out into six pieces of 16 mmφ, which were further dried at 100°C under reduced pressure (1.3 kPa) for 2 hours and pressed with a press until the target electrode porosity (electrode thickness) was reached to prepare negative electrodes for evaluation. Six negative electrodes for evaluation were prepared for each Example and Comparative Example (except Comparative Examples 23 and 28), three of which were used for evaluation of the surface condition and electrolyte permeability, and the remaining three were used for evaluation of battery performance (initial coulombic efficiency, internal resistance). In addition, Comparative Examples 23 and 28 are electrode compositions and electrodes (negative electrodes) that do not contain either compound (A) or (comparison A). The electrodes (negative electrodes) of Comparative Examples 23 and 28 were prepared in the required numbers.
[0069] [Table 4]
[0070] [Table 5]
[0071] <Evaluation of the surface condition of the slurry electrode> For each Example and Comparative Example, the surface state of the positive electrode or negative electrode for evaluating electrolyte permeability obtained by the above-mentioned electrode (positive electrode) or electrode (negative electrode) preparation was visually observed, and the surface state (degree of surface roughness) of the electrode was evaluated according to the following criteria using electrodes that had the same electrode active material and did not contain either compound (A) or (comparison A) (Examples 1 to 12, Comparative Examples 1 to 8, 10 to 11: Comparative Example 9, Examples 13 to 15, Comparative Examples 12 to 13: Comparative Example 14, Examples 16 to 27, Comparative Examples 15 to 22, 24 to 25: Comparative Example 23, Examples 28 to 30, Comparative Examples 26 to 27: Comparative Example 28) as a comparison. The results are shown in Tables 2 to 5. [Evaluation Criteria] ◎: The surface is smoother and has fewer irregularities than the comparison electrode. ○: The degree of surface roughness is the same as that of the comparison electrode. ×: The surface is rougher and has more projections and recesses than the comparative electrode. In addition, ◯ is an acceptable level for practical use, and ⊚ is even more preferable. A good surface condition of the electrode (low surface roughness) also leads to improved performance of the lithium-ion battery.
[0072] <Evaluation of electrolyte permeability (electrolyte permeation time) (slurry electrode)> 50 μL of the electrolyte was dropped onto the electrode (positive or negative electrode) for evaluating electrolyte permeability prepared above, and the time (min) until the electrolyte permeated into the electrode was measured. The shorter the time until the electrolyte permeated, the better the permeability. When the electrolyte is dropped onto the electrode for evaluating electrolyte permeability, the color of the part where the electrolyte is dropped becomes darker. When the electrolyte is absorbed into the electrode, the color returns to the original color, so the time (minutes) until the color of the electrode for evaluating electrolyte permeability returns to the original color was measured and defined as the electrolyte permeation time (minutes). The electrolyte permeation time (minutes) was compared with electrodes (Examples 1 to 12, Comparative Examples 1 to 8, 10 to 11 for Comparative Example 9, Examples 13 to 15 for Comparative Examples 12 to 13 for Comparative Examples 14, Examples 16 to 27, Comparative Examples 15 to 22, 24 to 25 for Comparative Example 23, Examples 28 to 30, Comparative Examples 26 to 27 for Comparative Examples 28) with the same electrode active material and no additive under the same electrode porosity (%), and the results are shown in Tables 2 to 5, which show the results evaluated according to the following criteria. Note that the electrolyte permeation time of three electrodes for each Example and Comparative Example was measured in units of one second, and the arithmetic average value was defined as the electrolyte permeation time (minutes). For each of the Examples and Comparative Examples, the electrolyte permeability was evaluated for two types of electrolyte: electrolyte 1 (EC / DEC = 1 / 1 (volume ratio), LiPF61M, viscosity (25°C): 6.9 mPa.s) and electrolyte 2 (EC / PC = 1 / 1 (volume ratio), LiFSI 1.73M, viscosity (25°C): 10.5 mPa.s). In the above, EC stands for ethylene carbonate, DEC stands for diethyl carbonate, and PC stands for propylene carbonate. LiPF6 stands for lithium hexafluorophosphate, and LiFSI stands for lithium bis(fluorosulfonyl)imide. [Evaluation Criteria] ◎: The electrolyte penetration time (min) was 0.3 times or less than that of the comparison electrode (min) (a reduction of 70% or more). Good: The electrolyte penetration time (minutes) was more than 0.3 times but less than 0.6 times the electrolyte penetration time (minutes) of the comparison electrode (reduced by 40% or more but less than 70%). △: The electrolyte penetration time (min) was more than 0.6 times but less than 0.8 times the electrolyte penetration time (min) of the comparison electrode (reduced by 20% to less than 40%). ×: The electrolyte penetration time (min) was more than 0.8 times the electrolyte penetration time (min) of the comparison electrode (the time reduction effect was less than 20%).
[0073] <Production of batteries for charge / discharge tests (slurry electrodes)> (Preparation of batteries using positive electrodes for evaluating battery performance of Examples 1 to 15 and Comparative Examples 1 to 14) The positive electrodes for evaluating battery performance of Examples 1 to 15 and Comparative Examples 1 to 14, a separator [product name "#3501", manufactured by Celgard], and the negative electrode for evaluating battery performance of Comparative Example 23 were stacked in this order, and electrolyte 1 (EC / DEC=1 / 1 (volume ratio), LiPF61M) was injected, followed by vacuum lamination to prevent oxygen from entering, to produce lithium ion batteries as batteries for charge / discharge tests using the positive electrodes for evaluating battery performance of Examples 1 to 15 and Comparative Examples 1 to 14, respectively. Three lithium ion batteries were produced for each Example and Comparative Example.
[0074] (Preparation of batteries using negative electrodes for evaluating battery performance of Examples 16 to 30 and Comparative Examples 15 to 28) The positive electrode for battery performance evaluation of Comparative Example 9, a separator [product name "#3501", manufactured by Celgard], and the negative electrodes for battery performance evaluation of Examples 16 to 30 and Comparative Examples 15 to 28 were stacked in this order, and electrolyte 1 (EC / DEC = 1 / 1 (volume ratio), LiPF61M) was injected, followed by vacuum lamination to prevent oxygen from entering, to produce lithium ion batteries as batteries for charge / discharge tests using the negative electrodes for battery performance evaluation of Examples 16 to 30 and Comparative Examples 15 to 28, respectively. Three lithium ion batteries were produced for each Example and Comparative Example.
[0075] <Charge / discharge test: Measurement of initial coulombic efficiency (slurry electrode)> The initial performance of the lithium ion battery prepared as a charge / discharge test battery was evaluated at 25° C. using a charge / discharge measuring device “HJ-SD8” (manufactured by Hokuto Denko Corporation) in the following manner. Using the constant current constant voltage charging method (also known as CCCV mode), the battery was charged to 0.0V at a current of 0.05C, and then charged while maintaining 0.0V until the current value reached 0.0025C. After a 10-minute break, the battery was discharged to 1.5V at a current of 0.05C. The charged capacity was defined as [initial charge capacity (mAh)], and the discharged capacity was defined as [initial discharge capacity (mAh)]. The initial coulombic efficiency (%) was calculated by the following formula, and the results are shown in Tables 2 to 5. For each example and comparative example, three batteries were measured and the initial coulombic efficiency (%) was calculated, and the arithmetic mean value was used as the analysis value. [Initial coulombic efficiency (%)] = [Initial discharge capacity] ÷ [Initial charge capacity] × 100
[0076] <Evaluation of internal resistance of cells (batteries for charge / discharge tests) (slurry electrodes)> Each lithium ion battery after the charge and discharge test was used as an evaluation cell. It was charged at 1C to 4.2V with CC-CV (cutoff current 0.01C), and after one hour of rest, it was discharged at 0.1C to 2.5V. The voltage immediately before discharging was V0, the voltage 10 seconds after discharging was V1, and the current during discharging was I1, and the internal resistance of each cell was evaluated by taking (V1-V0) / I1 as the direct current resistance (DCR). Note that for each example and comparative example, three batteries were measured, and the arithmetic average value was used as the analysis value. DCR (Ω cm 2 ) is preferable since it reduces the internal resistance.
[0077] From Tables 2 to 5, it can be seen that the electrodes (slurry electrodes) of Examples 1 to 30 have a short electrolyte permeation time (fast electrolyte permeation rate) and high electrolyte permeability. Furthermore, it can be seen that the surface condition of the electrodes is good (◎ or ◯). In addition, the initial coulombic efficiency and internal resistance of the batteries of each Example are comparable to those of batteries not containing either compound (A) or (comparison A) (Comparative Examples 9, 14, 23, or 28), and it can be seen that the inclusion of compound (A) does not adversely affect the performance of these batteries.
[0078] (Examples 31 to 35, Comparative Examples 29 to 31: Preparation of Dry Electrode (Dry Positive Electrode)) NCA935 parts by weight as a positive electrode active material, acetylene black [Denka Co., Ltd., "Denka Black Li100"] 15 parts by weight as a conductive assistant, and PTFE (Daikin Industries, Ltd., "Polyflon PTFE F-104") 50 parts by weight as a binder resin were weighed, and pre-mixed at room temperature with a universal mixer high-speed mixer FS25 [Earth Technica Co., Ltd.] (50 rpm, 15 minutes), and then mixed with a high-speed mixer (500 rpm, 1 minute). Then, the compound (A) or (comparison A) in the weight parts shown in Table 6 was added, and further mixed with a universal mixer high-speed mixer FS25 (5000 rpm, 3 minutes, 80 ° C.) to obtain a positive electrode composition. The positive electrode composition obtained above was formed into a bulk shape (thickness about 1.5 mm) and rolled into a sheet. The rolling was performed by heating to 80°C. The rolled sheet obtained earlier was then folded in two to be crushed roughly, and then formed into a bulk shape again, and then rolled into a sheet shape using a metal roll on a flat plate, thereby promoting fibrillation. This process was repeated four times. Then, by further rolling, a dry positive electrode sheet with a thickness of 500 μm was obtained. Furthermore, the dry positive electrode sheet was cut out and placed in a press machine for rolling. Furthermore, a load of 5 kN was repeatedly applied to adjust the thickness, thereby obtaining a dry electrode. The gap was adjusted so that the final electrode thickness was about 200 μm. The electrode thickness of each of the obtained electrodes (positive electrodes) was measured with a film thickness meter (manufactured by Mitutoyo) and is shown in Table 6. The electrode thickness was determined as the average value of the thicknesses measured at three random locations. In addition, Comparative Example 31 is a positive electrode composition and an electrode (dry positive electrode) that do not contain either compound (A) or (comparison A). The required number of electrodes of Comparative Example 31 were prepared.
[0079] <Evaluation of electrolyte permeability (electrolyte permeation time) (dry electrode)> Regions in which the thickness variation was within 5% were sampled in a size of 25 mm square from the dry electrodes produced in Examples 31 to 35 and Comparative Examples 29 to 31 to prepare dry electrodes for permeability evaluation. This dry electrode for permeability evaluation was used as a test piece, and the electrolyte permeability was evaluated using the same evaluation method and criteria as in the case of the above slurry electrode, except that a dry electrode containing neither compound (A) nor (comparison A) (Comparative Example 31) was used as the comparison object. The results are shown in Table 6.
[0080] (Preparation of battery (half cell) for charge / discharge test (dry electrode) Half cells for charge / discharge tests were produced using the dry electrodes produced in Examples 31 to 35 and Comparative Examples 29 to 31 as positive electrodes. From the positive electrode side, carbon-coated aluminum foil as a positive electrode current collector, the above-mentioned dry electrode (positive electrode), a separator [product name "#3501", manufactured by Celgard], lithium metal foil as a counter electrode (negative electrode) [manufactured by Honjo Metals Co., Ltd.], and copper foil as a negative electrode current collector were stacked, and electrolyte 1 (EC / DEC = 1 / 1 (volume ratio), LiPF61M) was injected, followed by vacuum lamination to prevent oxygen from entering, to prepare a lithium ion battery for charge / discharge test. Three lithium ion batteries were prepared for each of the examples and comparative examples.
[0081] <Charge / discharge test: Measurement of initial coulombic efficiency (dry electrode)> For the lithium-ion battery for charge / discharge test using the above-mentioned dry electrode as the positive electrode at 25°C, the initial performance of the lithium-ion battery was evaluated using a charge / discharge measuring device "HJ-SD8" [manufactured by Hokuto Denko Corporation] in the same manner as for the battery using the above-mentioned slurry electrode. The results are shown in Table 6.
[0082] <Evaluation of internal resistance of cells (batteries for charge / discharge tests) (dry electrodes)> The lithium ion batteries using each dry electrode as a positive electrode after the charge / discharge test were used as evaluation cells, and the internal resistance of each cell was evaluated in the same manner as for the battery using the slurry electrode. The results are shown in Table 6.
[0083] [Table 6]
[0084] From Table 6, it can be seen that the electrodes (dry electrodes) of Examples 31 to 35 have a short electrolyte permeation time (fast electrolyte permeation speed) and high electrolyte permeability. In addition, the initial coulombic efficiency and internal resistance of the batteries of each Example are comparable to those of a battery (Comparative Example 31) that does not contain either compound (A) or (comparison A), and it can be seen that the inclusion of compound (A) does not adversely affect the performance of these batteries.
Claims
1. An electrode composition for a lithium ion battery, comprising a compound (A) which is an ethylene oxide adduct of an alkyl alcohol having an alkyl group having 1 to 4 carbon atoms, The electrode composition for a lithium ion battery, wherein the ratio of the number of carbon atoms in the alkyl group in the compound (A) to the average number of moles of ethylene oxide added [number of carbon atoms in the alkyl group / average number of moles of ethylene oxide added] is 0.008 to 0.
200.
2. The electrode composition for a lithium ion battery according to claim 1, wherein the compound (A) has an HLB value of 18.0 or more.
3. The lithium ion battery electrode composition according to claim 1, wherein the content of the compound (A) is 0.001 to 2% by weight based on the weight of the lithium ion battery electrode composition.
4. A lithium ion battery electrode obtained by compression molding the lithium ion battery electrode composition according to any one of claims 1 to 3.
5. A lithium ion battery comprising the lithium ion battery electrode according to claim 4.
Citation Information
Patent Citations
Lithium ion secondary battery and electrode for same
JP2008027633A
Negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2012151088A
Negative electrode for lithium ion secondary battery and lithium ion secondary battery
JP2020053282A
Cited By
Image forming apparatus
US12474654B2